Biochar Is Not Durable for Remediation of Heavy Metal-Contaminated Soils Affected by Acid-Mine Drainage - Junhao Qin; Xi Wang; Jidong Ying; Chuxia Lin (Toxics, 2022)
Biochar is a soil conditioner for enhancing plant growth and reducing plants’ uptake of heavy metals. However, the protonation of biochar surfaces in acid soils can weaken the capacity of biochar to reduce the phytoavailability of soil-borne heavy metals over time. The aim of this study was to test this hypothesis by performing a plant-growth experiment with five harvest cycles to examine the durability of rice-straw biochar for the remediation of an acidic-mine-water-contaminated soil. The application of the biochar significantly reduced the phytoavailability of the heavy metals and inhibited the plant uptake of cationic heavy metals but not anionic Cr. The beneficial effects of the biochar were weakened with the increasing number of harvest cycles caused by the gradual protonation of the biochar surfaces, which resulted in the desorption of the adsorbed heavy metals. The weakening capacity of the biochar to reduce the heavy-metal uptake by the vegetable plants was more evident for Cu, Zn, and Pb compared to Ni and Cd. The experimental results generally confirmed the hypothesis. It was also observed that the bioaccessible amount of various metals in the edible portion of the vegetable was also reduced as a result of the biochar application.